A study of institutional origins and change in a Canadian urban commons. Issue 2 (September 2015) - Robson, James P.; Sinclair, Andrew J.; Diduck, Alan P.
Kenora is a small city located in northwestern Ontario, Canada. The study presented here focuses on Tunnel Island, 300 acres of forested land adjacent to Kenora's downtown. The island is used and valued by both city residents and members of three nearby Ojibway nations. As a multiple-use, common-pool resource accessed by different groups for a range of non-extractive activities, the site has become an experiment in multicultural commons governance, and presents an excellent opportunity to examine the origins and development of institutions for managing collective environmental resources in an urban setting. Using participant observation, internet- and field-based user surveys, and semi-structured interviews, our research finds that grassroots 'governance' of the site is emerging through subtle processes of individual and social construction, with the strategies and norms (codes of conduct) employed by users providing relative harmony on the trails, which suggests functioning commons institutions. Nevertheless, values-based and epistemic tensions exist among users, pointing to governance challenges for planned joint management of the site, and specifically the need to develop formal, legitimate, and yet flexible and inclusive arrangements that can operate in conjunction with the social practice of existing users.